Dynamics of Russian television news broadcasting in the context of the reflection of the COVID-19 pandemic - Rassyhovich Gazizov, Ramis (2020)
This article presents an analysis of the functioning of the leading Russian television channels in March - May 2020, during the coverage of the problem of coronavirus infection. The informational priorities of channels and the linguistic aspects of presentations are investigated. The stages of coverage of the problem are determined, as well as the actors that dominate the information space. Attention is drawn to the application of event interpretation techniques, the implementation of new forms of television broadcasting in Russia under the influence of a new virus pandemic. Analyzed the information issues that appeared on television channels: “First”, “Russia 1”, “Russia 24”, “NTV”. The reports of Murat Zaripov on Rossiya 1 channel, Mikhail Chernov on NTV channel, which touched upon current issues of the pandemic in Russia and the central problem are rather clearly presented: the restrictions of the authorities introduced to save the lives of citizens and people's unwillingness to comply with the restrictions are analyzed. A personality protest aimed at realizing one’s own desires and ignoring social norms has become one of the most characteristic phenomena during the coverage of the topic of coronavirus infection. The most frequent images are distinguished: “doctors - rescuers”, violators, volunteers. New terms are formulated and updated: medical authorities, plateau, self-isolation index, self-isolation, self-preservation. The determination of these and other data allows us to better understand the specifics of coverage of the topic of a new coronavirus infection by leading Russian television companies.